Solid-phase extraction for RP-HPLC/UV determination of ziprasidone at presence its main metabolite in urine - Sophia Davydovych, Iryna Halkevych, Olha Korobova, Svitlana Humenyuk (Journal of Applied Pharmaceutical Science, 2017)
The rapid and accurate high-performance liquid chromatography method with ultraviolet detection (210 nm) for the determination of Ziprasidone in rat urine was developed. Simple protocol of solid-phase extraction of ziprasidone from urine sample at presence its main metabolites was worked out. Vardenafil was used as an internal standard. Reversed phase column LUNA® C18(2) 100A 250 mm × 4.6 mm × 5 μm was used with an isocratic mobile phase consisting of acetonitrile : 0.5 % triethylamine (30: 70) and 0.1 M phosphoric acid (pH 2.5). Developed conditions of HPLC analysis provide high efficiency of a system and good separation of analytes. The method was validated and applied to rat urine samples after modelling intoxication. The intra- and inter-day precision was ≤ 15% with recovery about 95 %. A linear range of 1 μg/mL to 200 μg/mL was established. LOD and LOQ were 0.2 and 0.5 μg/mL, respectively. Obtained results indicate that the described procedure of sample pretreatment with automatization possibility allows obtaining good results for ziprasidone. This method is sensitive, precise and repeatable enough to be used in toxicological casework.
Keywords: Ziprasidone, Solid-phase extraction, HPLC, UV-spectroscopy.